The enrichment of rotifers (Brachionus plicatilis) and Artemia franciscana with taurine liposomes and their subsequent effects on the larval development of California yellowtail (Seriola lalandi). (13th May 2015) - Hawkyard, M.; Stuart, K.; Langdon, C.; Drawbridge, M.
Abstract: Taurine is an essential or conditionally essential nutrient for many species of marine fish, especially during early development. There is growing evidence that marine fish larvae benefit from taurine‐enriched rotifers; however, it is unknown if larvae benefit from taurine‐enriched Artemia . We investigated the effects of taurine‐enriched rotifers ( Brachionus plicatilis ) and Artemia franciscana on the growth and whole‐body taurine concentrations of California yellowtail ( Seriola lalandi ; CYT) larvae. The approach used in this study was to encapsulate taurine within microparticles (liposomes), which were then fed to rotifers and Artemia . We found that feeding taurine liposomes to rotifers and Artemia resulted in taurine concentrations in these prey species that were similar to or above those previously reported in copepods. At the end of the rotifer phase, CYT larvae fed taurine‐enriched rotifers showed increased growth (final dry weights; DW) and had higher whole body taurine concentrations when compared to larvae fed unenriched rotifers. At the end of the Artemia phase, CYT whole body taurine concentrations varied among dietary treatments. Larval lengths and DWs were not significantly different among treatments at the end of the Artemia phase, suggesting that the taurine concentrations of unenriched Artemia were sufficient to support the growth of CYT larvae.